Study of Membrane Transport for Hemodiafilter and Reverse Osmosis Module - Sekino, Masaaki (Journal of Membrane and Separation Technology, 2013)
As a typical membrane technology by which the solute substances are separated from a solution, hemodiafilter and reverse osmosis module are studied, in particular regarding the solute transport through the membrane. The solute transport equation, as a key point of this paper, could be derived from the modified Kedem-Katchalsky equation combined with Film theory model. As the next key point for the numerical analysis, the solute transport equation was inserted into the previous module model, and the differential equations composing this module model were converted to the difference equations calculated with a nonlinear secant method. Then the solute concentration profiles of the membrane and the boundary layers in the hemodiafilter and the reverse osmosis module were obtained to visually illustrate in Figures 3 to 6. Finally, it was clear that the occurrence of concentration polarization in the boundary layer is dependent on values of the membrane parameters, including solute permeability (Pm) and reflection coefficient (σ), the ultrafiltration flux (Jv) and the mass transfer coefficient (k).